2022
DOI: 10.1186/s13643-022-02073-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medical cannabis on cognitive functions: a systematic review

Abstract: Background Cannabis-based medicines are widely used in the treatment of a number of medical conditions. Unfortunately, cognitive disturbances are often reported as adverse events, although conversely, cognitive improvements have been reported. Hence, the objective of the present study was to identify, critically appraise and synthesise research findings on the potential impact of cannabis-based medicines on cognitive functioning. Methods Four datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…THC, the psychoactive component in cannabis known for the "high," on the other hand, has been linked to deleterious effects on cognitive function and memory [ 27 ]. Multiple studies have reported a wide range of CNS effects on the administration of THC [ 28 , 29 ].…”
Section: Reviewmentioning
confidence: 99%
“…THC, the psychoactive component in cannabis known for the "high," on the other hand, has been linked to deleterious effects on cognitive function and memory [ 27 ]. Multiple studies have reported a wide range of CNS effects on the administration of THC [ 28 , 29 ].…”
Section: Reviewmentioning
confidence: 99%
“… Bolla et al (2002) found in their study that dose-dependent neurocognitive impairment persisted after 28 days of abstinence in heavy young users. Furthermore, there is also evidence that adults who initiated regular cannabis use in adolescence may have structural and functional alterations of the CNS ( Wieghorst et al, 2022 ).…”
Section: Side-effectsmentioning
confidence: 99%
“…• Impairment of a wide range of cognitive functions in a dose-relation manner (Broyd et al, 2016;Lorenzetti et al, 2016;Wieghorst et al, 2022) • Long-term brain functional and structural alterations (Cousijn et al, 2012;Broyd et al, 2016;Meier et al, 2022) • Sedation (Lynch and Campbell, 2011;Borgelt et al, 2013;Kuhathasan et al, 2019) Frontiers in Pharmacology frontiersin.org…”
Section: Effect On Cardiovascular Systemmentioning
confidence: 99%
“…Cognitive dysfunction is commonly reported by Long COVID patients [10]. CBD has the potential to impact brain function [79] and although CBD has been shown to improve cognition in preclinical models of cognitive impairment [80], some uncertainty remains for the potential effects of CBMPs on cognitive function due to the heterogeneity of constituents and limitations across the studies [81]. An improvement in cognition after 4 weeks of treatment with a high-CBD CBMP has been demonstrated [70] and a small clinical trial of the CBMP nabiximols in ADHD demonstrated a trend towards significance in favour of the CBMP for improving cognitive performance and activity level after 6 weeks of treatment [82].…”
Section: Cognitive Dysfunctionmentioning
confidence: 99%